Pemberdayaan Ekonomi Desa Sigar Penjalin melalui Inovasi Sabun Ketapang dan Digitalisasi Wisata Komunitas - Elyakim Nova Supriyedi Patty; Sahdan Saputra; Lalu Busyairi Muhsin; Erin Ryantin Gunawan; Diswandi (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
This community service program aimed to enhance the economic empowerment of the Sigar Penjalin Village community through the innovation of ketapang (Terminalia catappa) leaf-based soap and the digitalization of community-based tourism. The program employed a Participatory Action Research (PAR) approach, actively involving local stakeholders in the stages of problem identification, planning, implementation, and evaluation. The activities included training on the formulation and production of herbal soap, product packaging and branding, as well as capacity building in digital marketing through social media platforms. The results indicated a significant improvement in community skills related to value-added product development and digital promotion strategies. Furthermore, the initiative contributed to diversifying local income sources and reducing dependency on traditional economic sectors. The integration of local natural resources with digital technology fostered greater community awareness, participation, and sustainability in economic development. Overall, this program demonstrates that combining local resource innovation with digital transformation can serve as an effective strategy for strengthening rural economies and promoting community resilience.